(untitled) (European Journal of Teaching and Education, 2024)
While some teachers enthusiastically embrace active learning as an effective means of engaging students in the classroom, many still prefer to stick to traditional teaching methods. Many teachers are reluctant to introduce active learning techniques, mainly because they are concerned about their practicality, especially when students have limited prior knowledge of the subject. They believe that active learning requires a high level of commitment from teachers and students and that implementing these modern teaching methods is hindered by institutional constraints. This scenario is particularly evident in Kosovo, where implementing the necessary changes is a major challenge, even though the current curriculum based on competencies favors this, making the required changes presents a major problem. This study aimed to understand how teachers perceive the benefits and barriers of using active learning methods with primary school students. Overall, respondents tended to rate the benefits of active learning more favorably than its constraints. However, there are differences between respondents in terms of effectiveness and feasibility, which emphasizes the nuanced nature of active learning, where benefits are recognized alongside the challenges.